Analisis Titer dan Subtipe Antibodi pada Inkompatibilitas ABO yang Menyebabkan Hemolytic Disease of Fetus and Newborn - Sheila Nurrahmah; Heri Wibowo; Ria Syafitri Evi G (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Hemolytic disease of the fetus and newborn (HDFN) is a type of anemia in the fetus or newborn. Clinical features of HDFN such as hepatosplenomegaly, liver failure, ascites, at birth die from heart failure to brain damage. One of the most common causes is incompatibility of blood groups such as ABO. Differences in clinical manifestations that occur in HDFN are caused by differences in antibody titers and IgG subtypes.Objective: The aim of this study was to determine the anti-A and anti-B antibody titers and the types of immunoglobulins that affect HDFN due to ABO incompatibility.Methods: The sample used in this study was blood and umbilical cord blood from 30 pairs of mother-babies who had different blood groups. Titration examination by tube method and IgG subtype by ELISA method were performed on maternal samples.Results: The correlation of total bilirubin levels with maternal Anti-A and Anti-B titers are p= 0.023 and p= 0.001, in addition there are significant increase in OD of Anti-A IgG1 and Anti-B IgG1 againts elevated infant bilirubin levels.Conclusion: IgG titers >8 causing hyperbilirubinemia, but no jaundice and IgG titers >16 causing hyperbilirubinemia to jaundice. The IgG subtype that plays a more role in causing clinical problems is IgG1.